An Updated Definition of Plastic Surgery. Issue 6 (December 2022) - Li, Qingfeng; Wang, Wenjin; Zan, Tao; Xiang, MengPing; Pu, Lee L. Q.; Schaefer, Dirk J.; Ohjimi, Hiroyuki
Abstract: Modern medicine tends to provide comprehensive medical services based on disease or pathological features. As a result, the overlap between plastic surgery and other surgical departments greatly deepened. What was exclusively done by plastic surgeons are nowadays frequently practiced by other surgeons as well. Thus, generating confusion as to whether plastic surgery is an independent subject or a tool. Therefore, in this new era of modern medicine, it is necessary to reconsider the definition of plastic surgery.